PERLINDUNGAN KONSUMEN DALAM EKONOMI SYARIAH : IMPLIKASI TERHADAP PRAKTIK BISNIS DI INDONESIA: Islamic Syariah - Dina Khairunnisa; Selly Salsabila (Jurnal Keuangan dan Perbankan Syariah, 2025)
Purpose: This study aims to analyze consumer protection in sharia business practices in Indonesia, particularly in ensuring justice, honesty, and transparency amid the rapid development of the sharia economy and the challenges of the digital era. Design/methodology/approach: This research uses a literature review method by collecting, examining, analyzing, and synthesizing relevant scientific sources, including journals, books, articles, and previous research reports related to sharia economics and consumer protection. Research Findings: The study finds that the principles of justice, honesty, and transparency are not only moral values but also practical foundations that strengthen interactions between business actors and consumers. Although Indonesia already has a sufficient legal framework for consumer protection, its implementation has not fully aligned with sharia economic principles. Strengthening regulation harmonization, consumer education, and supervision is essential to ensure consumer protection reflects Islamic values. Contribution/Originality/Novelty: This study contributes by offering a conceptual synthesis that integrates consumer protection regulations with core sharia economic principles. It highlights the urgency of harmonizing legal policies and strengthening sharia-based supervision to create fair, transparent, and sustainable business practices in Indonesia.